2022
DOI: 10.3390/buildings12040424
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Influencing Factors of Carbon Emission in Public Buildings in China

Abstract: The rapid development of public buildings has greatly increased the country’s energy consumption and carbon emissions. Excessive carbon emissions contribute to global warming. This paper aims to measure the carbon emissions in the operation of public buildings, and to identify the multiple influencing factors of carbon emissions in operational public buildings. First, the spatial and temporal variation characteristics of carbon emissions from public buildings in 30 provinces of China from 2008–2019 are analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Xiang et al (2022c) developed a carbon emission index decomposition tool for the construction industry-PyLMDI. Du et al (2022) discussed the spatiotemporal distribution of carbon emissions from public buildings in 30 provinces in China using the GTWR model and believed that there were east-west differences in the carbon emissions of public buildings in various provinces in China. Li G J. et al (2022) studied the commercial buildings in China from 2001 to 2016 changes in carbon emission reduction in the operation phase and established an evaluation framework for emission reduction intensity, emission reduction amount, and carbon emission reduction rate for the decomposition of carbon intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al (2022c) developed a carbon emission index decomposition tool for the construction industry-PyLMDI. Du et al (2022) discussed the spatiotemporal distribution of carbon emissions from public buildings in 30 provinces in China using the GTWR model and believed that there were east-west differences in the carbon emissions of public buildings in various provinces in China. Li G J. et al (2022) studied the commercial buildings in China from 2001 to 2016 changes in carbon emission reduction in the operation phase and established an evaluation framework for emission reduction intensity, emission reduction amount, and carbon emission reduction rate for the decomposition of carbon intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Peng implemented a detailed planning of material savings and material resource utilization for green construction and refined management, which not only improved construction speed but also produced considerable economic benefits [18]. Du Zhuoqun et al identified multiple influencing factors related to carbon emissions from operating public buildings by measuring carbon emissions during their operation, and then explored the relationship between each influencing factor and carbon emissions [19]. The most comprehensive analyses are still found in theoretical research, and there are fewer data related to the actual construction process [20].…”
Section: Introductionmentioning
confidence: 99%
“…To further understand the change mechanism of carbon emissions, some scholars began to explore the influencing factors of carbon emissions, and the studies involved the influencing factors mainly include economic growth, population size, industrial structure, gross national income, environmental quality, technological progress, and urbanization level (Xu et al, 2014;Shi et al, 2019;Meng et al, 2018;Li et al, 2011), and some studies further analyzed the spatial spillover effects of the influencing factors on carbon emissions (Xin et al, 2018;Gong et al, 2022). Theoretical studies are the basis of practical studies, and some scholars focus on the strong industry characteristics of carbon emissions, so they have gradually launched studies on carbon emissions from transportation (Xie et al, 2017;Zhu et al, 2020;Dujmovic et al, 2022), agriculture (Ali et al, 2022;Huang and Gao, 2022), aviation (Han et al, 2022), construction (Du et al, 2021;Du et al, 2022), logistics (Zhang Y. et al, 2021), and tourism. Further, related scholars have incorporated the topic of carbon reduction into the analysis of specific regional issues in order to improve the practical application value, and the carbon emission problems of some special regions have been widely studied, such as river basins (Sun et al, 2021;Wang et al, 2021), large cities (Qian et al, 2022), industrial cities (Zhang C. et al, 2021), urban agglomerations (Cui et al, 2020), metropolitan areas (Benjamin and Marilyn, 2009;Thomas, 2013), rural areas (Zhang et al, 2014), ports (Gian et al, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%